1997
DOI: 10.1111/j.1469-8986.1997.tb02134.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological evidence for cross‐modal plasticity in humans with early‐ and late‐onset blindness

Abstract: It is commonly believed that sensory deprivation can lead to cross-modal reorganization in an immature but not in a mature brain. The results of the present study suggest, however, that plasticity between sensory modalities is possible even in adults: activity indicating involvement of parietal or occipital brain areas in pitch-change discrimination was found in individuals blinded after childhood. Event-related brain potentials of early blinded (before the age of 2 years), late-blinded (12-28 years of age), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(60 citation statements)
references
References 23 publications
6
52
0
2
Order By: Relevance
“…These authors hypothesized that the large amplitude of the P3 over occipital regions in the blind suggests that blind participants recruit more attentional resources in performing cognitive tasks than the sighted. These results were corroborated by findings by Kujala et al [16] who found a topography shift in the P3 to occipital sites in early and late blind participants.…”
Section: P3supporting
confidence: 81%
See 1 more Smart Citation
“…These authors hypothesized that the large amplitude of the P3 over occipital regions in the blind suggests that blind participants recruit more attentional resources in performing cognitive tasks than the sighted. These results were corroborated by findings by Kujala et al [16] who found a topography shift in the P3 to occipital sites in early and late blind participants.…”
Section: P3supporting
confidence: 81%
“…These results suggest that blind participants may be implementing early classification mechanisms for multisensory processing and recruiting visual cortical areas to enhance processing efficiency. Kujala et al [16] investigated the differences in auditory ERP topography between late blind, early blind, and sighted participants. They found that the N2 in late blind participants, as with early blind, showed a significant topographical shift to occipital electrode sites.…”
Section: Mismatch Negativity (Mmn) and N2 Componentsmentioning
confidence: 99%
“…This is not surprising in that the task was exclusively auditory and would therefore be unlikely to activate cells that are typically involved in multisensory integration. However, data have shown that in early blind individuals these regions become dominated by nonvisual systems and do not require visual stimulation to be activated [7,13,15,17,30]. This is clearly the case in subject ML.…”
Section: Discussionmentioning
confidence: 86%
“…This shows that traditionally "visua1" areas of the brain in individuals who have always been totally blind actually process tactile information. Crossmodal reorganization of brain functions may take place even after childhood: Visual brain areas are activated by tactile (Buechel et al 1998) and auditory (Kujala et al 1997) tasks in blind subjects who had had normal vision until puberty or adulthood. Whether this activity corresponds functionally to actual perception or information processing remains to be clarified.…”
Section: Goal Directed Meaning Connects Perception and Specificationmentioning
confidence: 99%